Effectiveness of ketamine in chronic low back pain patients - P Pradeep; T Amar Govind Rao (Asian Journal of Medical Research, 2012)
Background: To evaluate effectiveness of ketamine in chronic low back pain patients. Methodology: Sixty patients of chronic low back pain of both genders were divided into 2 groups of 30 each. Group ? patients were given 25 mg ketamine and group ?I patients were given 50 mg ketamine as adjunct to 40 mg triamcinolone in total 6 ml volume given epidurally. Pain was recorded using visual analogue scale (VAS). Side-effects were recorded. Results: The mean age in group I was 47.2 years and in group II was 48.4 years. The mean weight was 68.3 Kgs in group I and 65.2 kgs in group II. The mean height was 158.2 cm in group I and 154.6 cm in group II. A non- significant difference was observed (P> 0.05). The mean VAS at baseline in group I was 76.3 and in group II was 83.4. At 2 weeks, in group I was 47.2 and in group II was 55.6. At 4 weeks in group I was 45.6 and in group II was 43.7. At 8 weeks in group I was 39.8 and 34.0. At 12 weeks was 34.5 in group I and 33.2 in group II. The difference was non- significant (P> 0.05). Nausea was seen in 4 in group I and 2 in group II. Hallucinations was seen in 8 in group I and 12 in group II. Hypertension was seen in 1 in group I and 4 in group II and tachycardia was seen in 2 in group I and 6 in group II. A significant difference was observed (P< 0.05). Conclusion: Ketamine in dosage of 50 mg is effective as compared to 25 mg in chronic low back pain patients.